Cultural Encounters: Puppetry Performing Arts (Wayang) and Dangdut Music as a Reflection of India-Indonesia Integration - Bagaskara, Akbar; Rokhani, Umilia; Wahyuningsih, Septiana (International Journal of Culture and Art Studies, 2024)
The purpose of this research is to reveal the relationship or social and cultural influence of the Indian nation on the expression of performing arts (wayang) and dangdut music in Indonesia. The hope of this research is to increase public awareness of the identity of national performing arts and music, which is rarely realized to be heavily influenced by Indian culture. Specifically, the aspects examined in this research include changes in the content of stories from Indian epics in the adaptation of Indonesian performing arts, as well as dangdut music that adapts the energetic spirit of music and dance from India. The method used in this research is qualitative with primary data sources derived from scientific articles and books related to the research. The data validation analysis technique used in this research is triangulation. Triangulation is used as a means of comparing the amount of data, to determine its consistency and accuracy, which will be displayed in the research. The results of this study show that, the culture brought by India is not really one hundred percent imitated or copied by the Indonesian people. The author concludes that the hybridity that occurs between Indian and Indonesian culture actually forms a new innovation in the field of art itself or can also be called a new work. The Mahabharata and Ramayana stories, which were originally the source of puppetry, changed and adapted to Indonesian culture. As a result, there are many compositions of the two epics, character changes, and the emergence of new characters that do not exist in the Mahabharata and Ramayana themselves, such as the punakawan characters that are closely related to the spread of Islam in Indonesia. The same goes for dangdut, a music that was originally based on the character of Malay music from Indonesia, now transformed into a new genre called dangdut due to the influence of India, through political elements and the spread of Indian movies in the 20th century.